Left Threatened by Right: Political Intergroup Bias in the Contemporary Italian Context - Schepisi, Michael; Porciello, Giuseppina; Bufalari, Ilaria; Aglioti, Salvatore Maria; Panasiti, Maria Serena (Frontiers in Psychology, 2019)
Using different evaluation targets (i.e., politicians’ pictures, ideological words, items referring to features attributed to political ingroup/outgroup) we characterized the intergroup bias among political groups in the Italian context (Study 1-2-3) and tested a model that may account for the bias itself (Study 3). For all evaluation targets, left-wing participants -compared to right wing participants - showed a greater intergroup bias, expressing more negative emotions towards the outgroup. The process was influenced by a greater perceived threat of the outgroup. Conversely, right-wing participants expressed the bias only when presented with ideological words. Our results provide a detailed description of how intergroup bias in Italy is differently expressed by the two ideological groups depending on the targets used to represent the political counterpart. Moreover, the results show that the stronger bias expressed by left-wing participants is driven by perceived threat of the outgroup.